2015
DOI: 10.1249/mss.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Slower V˙O2 Kinetics in Older Individuals

Abstract: Thus, this review focuses on the concept that although V̇O₂ kinetics is often slower in the elderly, this slower increase in the rise of oxygen uptake during the exercise on-transient does not need to be considered an inevitable response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
(138 reference statements)
0
16
0
Order By: Relevance
“…V O 2 pulm kinetics, used as a proxy of V O 2 musc kinetics, seem to be slower in aged compared with younger subjects [2][3][4]11] (off kinetics only), [17,18,41,42], but depend on physical activity [2, 12 − 14, 25, 44]. The limitation of V O 2 kinetics in aged subjects can be ascribed to several mechanisms, which can be classified into either O 2 delivery and/or O 2 extraction, either centrally or peripherally mediated [24,38,39]. The O 2 extraction depends on the complex interplay between availability of O 2 at the mitochondria, adequate activation of enzymes, supply of substrates for oxidative phosphorylation and ATP synthesis in the working muscle cell [16].…”
Section: Abstract ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…V O 2 pulm kinetics, used as a proxy of V O 2 musc kinetics, seem to be slower in aged compared with younger subjects [2][3][4]11] (off kinetics only), [17,18,41,42], but depend on physical activity [2, 12 − 14, 25, 44]. The limitation of V O 2 kinetics in aged subjects can be ascribed to several mechanisms, which can be classified into either O 2 delivery and/or O 2 extraction, either centrally or peripherally mediated [24,38,39]. The O 2 extraction depends on the complex interplay between availability of O 2 at the mitochondria, adequate activation of enzymes, supply of substrates for oxidative phosphorylation and ATP synthesis in the working muscle cell [16].…”
Section: Abstract ▼mentioning
confidence: 99%
“…Slowed HR kinetics are one possible limiting factor for O 2 delivery and may explain slowed V O 2 pulm kinetics [13,16,17] though only if the arteriovenous oxygen difference (avDO 2 ) is not sufficient to compensate for slowed HR kinetics [7]. The limiting factors of V O 2 kinetics are under discussion [16,21,28,29,38,43]. A differential analysis of cardiorespiratory kinetics should be performed for the detection of individual limitation of V O 2 kinetics.…”
Section: Abstract ▼mentioning
confidence: 99%
“…Aging is accompanied by the development of chronic diseases, which makes it necessary to give greater attention to the elderly population [2]. Maximal oxygen consumption (VO 2max ) is recognized as one of the most important indicators in the prognosis of good health in older people [3] and it is used to predict survival in patients with cardiovascular disease [4][5][6][7][8]. A decrease in VO 2max is one of the clearest consequences of aging since, from the age of 30, it decreases by 10% every 10 years in people with a sedentary lifestyle [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the O 2 kinetics response in young and older adults have regularly shown slower τ O 2 values in the aging population (Chilibeck et al, 1996 ; DeLorey et al, 2004 ; Murias et al, 2010 ; Gravelle et al, 2012 ). Although debate exists in relation to the mechanisms that control the rate of adjustment of oxidative phosphorylation (Grassi, 2001 ; Hughson et al, 2001 ; Poole and Jones, 2012 ; Murias et al, 2014 ; Murias and Paterson, 2015 ), there is a stronger consensus supporting the idea that, in older populations, the slower dynamic adjustment of O 2 is related to limitations within the O 2 transport system and, more specifically, in the O 2 provision to the active muscles which affects the matching of O 2 delivery to O 2 utilization (Murias et al, 2010 ; Poole and Jones, 2012 ). However, a slower adjustment of oxidative phosphorylation in older individuals is not always the case.…”
Section: Discussionmentioning
confidence: 99%